Analysis of Cholesterol Levels of Free-Range Chicken Meat With Turmeric Flour Supplementation - Dela Heraini; Yeti Rohayeti (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2025)
This study aimed to determine the effect of dietary turmeric (Curcuma longa) supplementation on the cholesterol profile of native chicken meat. Five treatments (control and four levels of turmeric inclusion) with five replications each were used. Data were analyzed using one-way ANOVA. The results showed that turmeric supplementation significantly affected meat cholesterol content (F = 16.302; p < 0.001). The highest cholesterol level was observed in the control group (67.06 ± 4.86 mg/100 g), while the lowest was in treatment 3 (41.57 ± 11.07 mg/100 g). Furthermore, crude protein and fat content of the meat also showed significant differences among treatments. These findings indicate that turmeric powder can be applied as a functional feed to produce native chicken meat with lower cholesterol content.